Large-Signal Simulation of 94 GHz Pulsed Silicon DDR IMPATTs Including the Temperature Transient Effect - Acharyya, Aritra; Banerjee, Suranjana; Banerjee, J. P. (Společnost pro radioelektronické inženýrství, 2012)
In this paper large-signal modeling and simulation has been carried to study the frequency chirping due to temperature transients and the large-signal power and efficiency of pulsed silicon Double-Drift Region (DDR) Impact Avalanche Transit Time (IMPATT) device operating at 94 GHz. A large-signal simulation method based on non-sinusoidal voltage excitation incorporating the transient thermal effect has been developed by the authors. Results show that the device is capable of delivering a peak pulsed power output of 17.5 W with 12.8% efficiency when the voltage modulation is 60%. The maximum junction temperature rise is 350.2 K for a peak pulsed bias current of 6.79 A with 100 ns pulsewidth and 0.5 percent duty cycle; whereas the chirp bandwidth is 8.3 GHz.
Keywords: Chirp bandwidth; frequency chirping; large-signal simulation; pulsed DDR IMPATT; temperature transients.